Hydroxytyrosol (HT) Analogs Act as Potent Antifungals by Direct Disruption of the Fungal Cell Membrane - Diallinas, George; Rafailidou, Nausica; Kalpaktsi, Ioanna; Komianou, Aikaterini Christina; Tsouvali, Vivian; Zantza, Iliana; Mikros, Emmanuel; Skaltsounis, Alexios Leandros; Kostakis, Ioannis K. (Frontiers in Microbiology, 2018)
Fungal infections constitute an emerging threat and a prevalent health problem due to increasing number of immunocompromised people and pharmacological or other treatments aiming at viral infections, cancer or allergies. Currently used antifungals suffer from inefficiency, toxic side effects and developing drug-resistance. Additionally, over the last two decades no new classes of antifungals have been approved, emphasizing the urgent need for developing a novel generation of antifungals. Here we investigate the antifungal activity of a series of chemically synthesized Hydroxytyrosol (HT) analogues. ΗΤ is one of the major phenolic compounds in olive oil, shown to possess radical-scavenging antioxidant, antiproliferative, proapoptotic and anti-inflammatory activities. No previous report has studied HT analogues as antifungals. We show that specific analogues have broad and strong antifungal activity, significantly stronger than the parent compound HT. Using A. nidulans as an in vivo cellular model system, we show that antifungal HT analogues have an unprecedented efficiency in fungal plasma membrane destruction. Importantly, antifungal HT analogues did not show toxicity in a mammalian cell line, whereas no resistance to HT analogues was obtained by standard mutagenesis. Our results open the way for the development of a novel, efficient and safer class of antifungals.